2012
DOI: 10.1001/archinternmed.2011.1032
|View full text |Cite
|
Sign up to set email alerts
|

Tests and Expenditures in the Initial Evaluation of Peripheral Neuropathy

Abstract: Background Peripheral neuropathy is a common disorder in which an extensive evaluation is often unrevealing. We sought to define diagnostic practice patterns as an early step in identifying opportunities to improve efficiency of care. Methods The 1996–2007 Health and Retirement Study (HRS) - Medicare Claims linked database was used to identify individuals with an incident diagnosis of peripheral neuropathy using ICD-9 codes and required no previous neuropathy diagnosis during the preceding 30 months. Focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…In evaluating a patient with DSP, at a minimum the clinical pattern of involvement, nerve conduction studies, and laboratory tests should be obtained to diagnose the condition and to identify potential treatable etiologies. 3,9 Recent studies have demonstrated that adequate diagnostic studies are often not performed in patients with peripheral neuropathy. 8 Neuropathy was selected as the topic because it is a clinical priority for neurology, has a high burden of illness, has demonstrated gaps in care with room for improvement, and has unexplained variations in care.…”
Section: Quality Improvement In Neurologymentioning
confidence: 99%
“…In evaluating a patient with DSP, at a minimum the clinical pattern of involvement, nerve conduction studies, and laboratory tests should be obtained to diagnose the condition and to identify potential treatable etiologies. 3,9 Recent studies have demonstrated that adequate diagnostic studies are often not performed in patients with peripheral neuropathy. 8 Neuropathy was selected as the topic because it is a clinical priority for neurology, has a high burden of illness, has demonstrated gaps in care with room for improvement, and has unexplained variations in care.…”
Section: Quality Improvement In Neurologymentioning
confidence: 99%
“…4 Unfortunately, the cost of evaluations can be prohibitive, and physicians often order high-cost, low-yield tests rather than low-cost, high-yield studies. 5 Despite the recent AAN recommendations and the publication of several clinical approaches to the evaluation of neuropathy, clinicians continue to order a wide variety of laboratory tests. [3][4][5][6][7] In this study, we evaluated the frequency of abnormal thyroid or rheumatologic results in the setting of a diagnosis of peripheral neuropathy.…”
mentioning
confidence: 99%
“…5 Despite the recent AAN recommendations and the publication of several clinical approaches to the evaluation of neuropathy, clinicians continue to order a wide variety of laboratory tests. [3][4][5][6][7] In this study, we evaluated the frequency of abnormal thyroid or rheumatologic results in the setting of a diagnosis of peripheral neuropathy. When the tests were abnormal, we assessed the frequency that the test changed the suspected etiology or management.…”
mentioning
confidence: 99%
“…We identified individuals with incident peripheral neuropathy diagnosed between 1998 and 2007, as previously described. 9 We defined an incident diagnosis in persons who had an International Classification of Diseases (ICD)-9 code of peripheral neuropathy in a Medicare claim and no previous neuropathy diagnosis during the preceding 30 months. We included all ICD-9 codes for peripheral neuropathy (354.5, 356.0-9, and 357.0-9).…”
Section: Populationmentioning
confidence: 99%
“…5 Interestingly, high-cost, low-yield tests such as MRIs of the neuroaxis are frequently ordered (23.2%), whereas low-cost, high-yield tests like glucose tolerance tests are rarely ordered (1%). 9 Furthermore, neurologists report that they would order more tests than internists when presented with the same clinical vignettes of distal symmetric polyneuropathy. 5 Specifically, neurologists reported the increased utilization of laboratory and electrodiagnostic testing, but not MRIs of the brain or spinal cord, which internists indicated that they would order more often.…”
mentioning
confidence: 99%